Penerapan Relaksasi Otot Progresif bagi Mahasiswa Keperawatan dalam Menurunkan Kecemasan Pasca Evaluasi Semester - Syokumawena, Syokumawena; Sulistini, Rumentalia; Mediarti, Devi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2024)
Anxiety can be experienced by everyone from young to old. Anxiety experienced by students often occurs when students are faced with learning evaluations and end-of-program evaluations. Anxiety cannot be avoided and must be faced. To be able to overcome it, various relaxation techniques can be used, one of which is progressive muscle relaxation. In this service activity involved 30 nursing students who had completed the semester evaluation. They were given this therapy and evaluated for anxiety before and after. The results obtained decreased the number of students who were still anxious, namely 6 people with mild anxiety categories. With this action, students are more relaxed and ready to follow the next learning.